The complete Blockchain professional course - Vijh, Mayank (Packt Publishing, 2019)
"Welcome to the Complete Blockchain Professional Course. People have heard about Blockchain, but they don't know what it is. This course has been designed to give you a thorough understanding of how the Blockchain technology is used as a solution to various industry-wide problems. This very comprehensive course explains all the Blockchain basics in an easy-to-understand way. To promote interactivity and clarity, we have provided various quizzes as a part of the modules; you will be able to master all important Blockchain-related topics. If you are passionate about Blockchain, then this course is for you!"--Resource description page